The Effectiveness of Aid under Post-Conflict Conditions: A Sector-Specific Analysis. Issue 4 (3rd April 2019) - Donaubauer, Julian; Herzer, Dierk; Nunnenkamp, Peter
Abstract: It is widely believed that foreign aid may help conflict-affected countries to recover after the termination of conflicts. However, the available empirical evidence supporting this view largely neglects the heterogeneous nature of aid. Drawing on the conflict database of the Uppsala Conflict Data Program, we address the hypothesis that the effectiveness of post-conflict aid differs between specific sectors. Our focus is on social and economic infrastructure which is most likely to suffer during conflict episodes so that the need for aid is particularly pressing in this area. We find fairly robust evidence that post-conflict aid is effective in improving social infrastructure. In contrast, aid appears to be ineffective in improving economic infrastructure.